Social Implications of Weight Bias Internalisation: Parents’ Ultimate Responsibility as Consent, Social Division and Resistance - Noonan-Gunning, Sharon (Frontiers in Psychology, 2019)
Responsibility is a moral quality of caring that is central to child health policies. In contemporary UK these policies are based on behavioural psychology and underpinned by individualism, an ideology central to neoliberal governance. Amid the complexities of “obesity” and inequalities, there is a multi-layered stigmatisation of parents as moral associates. Few studies consider the lived realities of food policy processes from the standpoint of class. This critical qualitative research draws on theorists who explain processes of power and class: Foucault, Gramsci, Bourdieu and Marx. Its objectives are: (a) to understand the lived experience of parents as they interact with food policy; (b) to explore how parents resist stigmatisation; and (c) to reflect on implications for policy and practice. Methods: Using purposive sampling, 31 ethnographically-informed interviews were carried out in a London borough, with policy actors: policymakers, implementers and parents as policy recipients, including 12 working-class mothers. Results: A core theme of “responsibilities” emerged with four interconnecting sub-processes that provide insight into how stigmatisation and resistance evolve through policy. Discussion: As have others, this study reveals the idea of responsibility as fundamental to the processes of soft power. Child health is a priority for participants and a “ruling idea”. The diffusion of responsibility throughout policy leads to confusion about where it lies. New subjectivities are formed in line with ideas of governmentality. Parents engage with policy at multiple sites that elicit symbolic violence, and stigma sows social divisions. Against this background, working-class parents are left in a state of cognitive dissonance between being made responsible (responsibilisation), and feeling responsible (self-blaming) for their children’s weight while lacking the material resources to provide an optimal nutritious diet. Resistance is interwoven and is essentially found in parents’ policy alternatives that diverge from UK government policy. Conclusion: Critical qualitative research using multiple theorists is valuable in understanding how parents interact with policy in a complex social world. With UK policy failing, useful insights are provided into how involving parents in policymaking might determine a meaningful collective responsibility, with a political ethic of care and unity between parents that would advance health equity